ANALYSIS OF THE INFLUENCE OF MOBILE BANKING SERVICE QUALITY ON THE LEVEL OF CUSTOMER SATISFACTION AT PT.BANK SUMUT KATAMSO SYARIAH BRANCH OFFICE - Muhammad Khoiri Gusmar; Isra Maulina; Mukhtasar Mukhtasar (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2023)
This study aims to determine the effect of each dimension of service quality, namely security, convenience and speed on the level of customer satisfaction at PT Bank Sumut Syariah Katamso Branch Office. The variables in this study are security, convenience, speed, and customer satisfaction. The independent variables (x) in this study include: Security (X1), Ease (X2), and Speed ​​(X3). For variable (Y) customer satisfaction. The method used in this study is a descriptive quantitative method. The population in this study are all customers of Bank Sumut who use mobile banking. The sample used was 99 respondents with a non-probably method with accidental sampling technique. The results showed that partially the security variable had a significant effect on the level of customer satisfaction with Tcount <Ttable 2.804 <1.985 with a significant level of 0.002 > 0.05. The convenience variable has a significant effect on the level of customer satisfaction with Tcount <Ttable 3.319 <1.985 with a significant level of 0.003 > 0.05. The speed variable has a significant effect on the level of customer satisfaction with Tcount < Ttable 3.432 < 1.985 with a significant level of 0.000 > 0.05. And simultaneously the variables of security, convenience and speed have a significant effect on the level of customer satisfaction, with Fcount >Ftable, 46, 469 > 2.70 with a significant value of 0.000 <0.05 at the Bank of North Sumatra, the Katamso Sharia Branch Office.